Clima organizacional para la competitividad empresarial del sector comercial de México Y Colombia (2018)
The research aimed to analyze the organizational climate for business competitiveness in the commercial sector of Mexico and Colombia, among these SAO and COPPEL. Epistemologically approach is critical rationalist, the type of research is descriptive, with a transverse non-experimental design. We used the technique of the survey using a structured questionnaire (39) items, applied to administrative staff fixed of the companies subject of study. It is concluded that the organizational climate dimensions used for business competitiveness in the commercial sector of Mexico and Colombia, are located in a moderately satisfactory category, it could identify the indicator structure as the most recurrent. According to the factors of enterprise competitiveness indicator is present innovation; and to contrast the theories the organizational climate as a factor in business competitiveness, they are oriented to autonomy, pressure and innovation. For this reason it is recommended to continue in the same line of investigation, but at the regional level, in such a way that they can compare the results in different cities of the region and conduct a comparative study.